Leadership and Organizational Commitment of Vietnamese Employees During the COVID-19 Pandemic - Trung Kien, Nguyen; Tsutomu, Konosu (VNU Journal of Science: Policy and Management Studies, 2023)
The COVID-19 pandemic hit the world as a massive and sudden shock. Organizations are having difficulties to complete their objectives while ensuring employees’ safety whereas employees are suffering from mental and psychological health concerns, in addition to work difficulties, consequently affecting their organizational commitment. In this context, organizations and employees look up to leaders for their responses. The present study tackles leadership and organizational commitment of Vietnamese employees during the COVID-19 pandemic using the quantitative methodology. Participants are 267 Vietnamese employees who are currently working under heavy restrictions. The findings show that transformational leadership is the most prominent leadership style in Vietnam during the pandemic, following by transactional leadership. Transformational leadership has a strong and positive relationship with organizational commitment. Transactional leadership has a moderate and positive relationship with organizational commitment. The relationship appears to be weak and negative in the case of passive/avoidant leadership. The outcomes of leadership, most notably leaders’ effectiveness in dealing with group and individual interests and members’ satisfaction also show a strong and positive correlation with organizational commitment. The present study also delivers recommendation to leaders that the aspect of individual consideration should receive more attention as it helps to ease members’ struggle during the crisis, increase their satisfaction, and consequently improve their organizational commitment. Keywords: Leadership, transformational leadership, transactional leadership, organizational commitment, COVID-19, pandemic.